The Problem of Ensuring the Quality of Services in Tourist Destinations. French, Spanish and German Solutions - Zajadacz , Alina; Stroik , Ewa; Śniadek , Joanna (Studia Oeconomica Posnaniensia, 2018)
Ensuring a high quality of services in tourist destinations requires creating a flexible system, capable of being continuously improved. In order to create such a system, the first step is to define its scope and function, as well as the quality standard it is supposed to maintain. In the end the process should end with the implementation of an Integrated Quality Management (IQM) system which is necessary for securing a competitive advantage. The aim of this paper is to present ideas and models of quality management in tourism. In the empirical part, the authors include chosen case studies of quality management and practices in the tourist services sector and improvement thereof. The paper points to examples of France, Spain and Germany, given their status as major tourist destinations, not only in Europe but on a worldwide scale as well. The main method of research was a query of documents, reports and government programs pertaining to the quality of tourist services in the years 2016-2018 (in the case of France, the researchers also conducted a number of in-depth interviews). The results were used to formulate observations concerning the key factors of IQM systems in European destinations. Those include: cooperation between all stakeholders in perfecting and implementing the devised standards; combining the concept of quality with balanced development, accessibility and safety of the destinations; as well as an in-depth analysis of the potential of given source markets (including their diversified segments).